4x-3x-10=-2

Simple and best practice solution for 4x-3x-10=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3x-10=-2 equation:


Simplifying
4x + -3x + -10 = -2

Reorder the terms:
-10 + 4x + -3x = -2

Combine like terms: 4x + -3x = 1x
-10 + 1x = -2

Solving
-10 + 1x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 1x = -2 + 10

Combine like terms: -10 + 10 = 0
0 + 1x = -2 + 10
1x = -2 + 10

Combine like terms: -2 + 10 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| (x^3)+6(x^2)+11x+6=0 | | x+2+x+x=6-3 | | F(x)=4x-9-x^3 | | 7k+6=69 | | 4-7(3x-1)=-4x+28 | | 127=(16*59.3/x)(16*9.9/x) | | p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 | | 10xwhat=990 | | 4x+6=4+3x | | 5t-9=31 | | 7k-5=30 | | 6a-5=43 | | -30-6a=2(1-7a) | | 7a^2-24a-4=0 | | 31+6n=-5(1-3n) | | 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x |

Equations solver categories